Peluang dan Tantangan Perbankan Syariah Terhadap Pembiayaan Pemilikan Properti Residensial di Indonesia - Annisa Rahima (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
This research aims to give a thorough review on the chance and challenge of sharia banking on residential property financing in Indonesia along with the contract used in giving the residential property financing. This research used study of literature and SWOT analysis. Study of literature is used in giving the review on the contract used in giving the residential property financing. SWOT analysis is used to explain the chance and challenge of sharia banking on residential property financing in Indonesia.From this research, it is found that akad murabahah is still very dominant by sharia banking in giving residential property financing. Here in after shariah banking in Indonesia has the opportunity to keep improving residential property financing. It is seen from the higher demand of society on the sharia residential property and profit sharing system that is accepted by society. This is reflected from the increasing of sharia banking offices and assets in Indonesia. As or the challenges faced by sharia banking is the less innovation of residential property financing contract given to customer and the lack of public knowledge on the sharia banking.